2020
DOI: 10.15252/msb.20209828
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of bypass suppression of essential genes

Abstract: Essential genes tend to be highly conserved across eukaryotes, but, in some cases, their critical roles can be bypassed through genetic rewiring. From a systematic analysis of 728 different essential yeast genes, we discovered that 124 (17%) were dispensable essential genes. Through whole‐genome sequencing and detailed genetic analysis, we investigated the genetic interactions and genome alterations underlying bypass suppression. Dispensable essential genes often had paralogs, were enriched for genes encoding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(101 citation statements)
references
References 103 publications
(182 reference statements)
8
92
1
Order By: Relevance
“…We next sought to identify the causal suppressor genes. As each of the mapped suppressor regions harbors tens of plausible candidate genes, we computationally prioritised them based on their functional connection to the query gene (Data S6, Methods, (van Leeuwen et al 2020)). We also included known general modifiers, such as MKT1 and HAP1 , that each affect the expression of thousands of genes (Fay 2013; Parts et al 2014; Albert et al 2014, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We next sought to identify the causal suppressor genes. As each of the mapped suppressor regions harbors tens of plausible candidate genes, we computationally prioritised them based on their functional connection to the query gene (Data S6, Methods, (van Leeuwen et al 2020)). We also included known general modifiers, such as MKT1 and HAP1 , that each affect the expression of thousands of genes (Fay 2013; Parts et al 2014; Albert et al 2014, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…However, this subcomplex would not assemble in the absence of the NSE3 gene, and the NSE1 mutant allele does not rescue a nse3Δ deletion mutant (Figure S6). Comparison of our suppressors with a systematic survey of bypass suppression of essential gene deletion mutants (van Leeuwen et al 2020), showed little overlap in the identified suppressable essential genes, suggesting that the vast majority of standing variation suppressors will depend on the presence of the TS allele.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations